Establishment and Production Costs for Southern Highbush Blueberry Orchards in Florida: Enterprise Budget and Profitability Analysis - Ariel Singerman; Marina Burani-Arouca; Jeffrey G. Williamson; Gary K. England (EDIS, 2016)
The United States is the world’s largest producer of blueberries. Florida’s blueberry production represents a small fraction of total US production, but blueberries are nevertheless an important and valuable crop in the state because Florida growers benefit from the nation’s earliest market window. In fact, the average price for blueberries received by growers in Florida during the last three years was 2.5 times the US average.